CALL for Widening Participation: Short Papers From EUROCALL 2020 2020
DOI: 10.14705/rpnet.2020.48.1186
|View full text |Cite
|
Sign up to set email alerts
|

Student preferences: using Grammarly to help EFL writers with paraphrasing, summarizing, and synthesizing

Abstract: This study explores students’ perceptions about using Automated Writing Evaluation (AWE), Grammarly (a paid version), as a complementary instructional tool to teach and support writing from sources. Participants were second-year students (n=37) at a public university in Japan. After in-class tasks aimed at teaching paraphrasing, summarizing, and synthesizing, students completed a survey that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
1
0
Order By: Relevance
“…They said that Grammarly can help find mistakes and notice plagiarism. Similar to what Lazic et al (2020) claimed, the results of Eyong's (2022) study found out that Grammarly plagiarism detectors are quite effective for minimizing plagiarism in graduate students' research procedures. In his research, Eyong (2022) also claimed that to discover and repair problems in their research work and to lower the likelihood of plagiarism, all students must use the Grammarly program during their research tasks.…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…They said that Grammarly can help find mistakes and notice plagiarism. Similar to what Lazic et al (2020) claimed, the results of Eyong's (2022) study found out that Grammarly plagiarism detectors are quite effective for minimizing plagiarism in graduate students' research procedures. In his research, Eyong (2022) also claimed that to discover and repair problems in their research work and to lower the likelihood of plagiarism, all students must use the Grammarly program during their research tasks.…”
Section: Introductionsupporting
confidence: 68%
“…Students in Wardani's (2022) study also noticed that one of the features of Grammarly Premium is checking the originality of the content in their writing. In the Premium version, the user also can check the plagiarism in their writing, this is stated by Lazic et al (2020). They said that Grammarly can help find mistakes and notice plagiarism.…”
Section: Introductionmentioning
confidence: 99%
“…The results in the present study also suggest that students with lower confidence in academic writing were more likely to use GAI technologies. Software such as Grammarly has been shown to increase students' confidence in areas such as essay writing and avoiding accidental plagiarism (Lazic et al 2020). Amigud and Lancaster (2019) identified that academic ability was related to students usage of essay mills.…”
Section: Discussionmentioning
confidence: 99%
“…Most EFL students have the problems in writing, such as a lack of grammar and limited vocabulary. Undergraduate L2 students often struggle with paraphrasing, summarizing, synthesizing, appropriate attribution, and referencing, which may reduce motivation in the L2 writing class (Lazic et al, 2020).…”
Section: Introductionmentioning
confidence: 99%